Analysis of Fiqh Syafi 'Iyyah on Interaction with Whatsapp after the Engagement (Case Study at Mudi Princess Samalanga) - Maisarah Maisarah; Afrizal Afrizal; Rahmiyati Rahmiyati (Budapest International Research and Critics University, 2021)
The engagement period is the time to get to know the prospective bride and groom so that they get the heart to carry out the marriage. In an important period of interaction made by the bride and groom. Moreover, in today's digital era there is no distance barrier to being able to communicate like the WhatsApp application. With a variety of features that can be used by potential partners after the engagement period. Before the marriage contract takes place, the prospective partner is still ajnabi and ajnabiyah whose boundaries need to be maintained. Therefore, further research is needed on interactions with WhatsApp after the engagement period at MUDI Putri Samalanga. With the habit of santriwati using late at night to interact with potential partners. So is the pattern of communication with WhatsApp in accordance with Syafi'iyyah fiqh as the book they study everyday. By using qualitative research methods with normative-empirical research types by conducting observations, interviews and documentation and analyzing using descriptive methods. So it was found that the female MUDI female students used WhatsApp by chatting, video calling and voice calling while still paying attention to the signs outlined in Islamic teachings as learned in classical books. They still maintain in writing the words and when speaking directly. Using words that are commonly used in general and speaking only as needed and still maintaining aurat by dressing modestly, wearing a headscarf, wearing a veil and wearing socks.